Antropologi Melihat Money Politics - Kartini Sjahrir (Antropologi Indonesia, 1999)
In the context of Indonesia's recent elections, money politics is generally seen in a negative light. The author discusses this issue from the standpoint of economic anthropology, and provides as historical explanation of how monetary system entered the local economic system and to what extent it influences the sociopolitical system. Added to the discussion are comparisons with other systems. She continues to show how political systems are viewed from the anthropological perspective, and ends by explaining the meaning of money politics and its practice in political activities.